Pendaftaran Tanah Untuk Keamanan Kepemilikan Hak Atas Tanah: Tinjauan Studi Literatur - Keumala, Dinda (UNES Law Review, 2023)
Land registration is an activity carried out to obtain legal certainty and provide security of ownership of land rights. The problem in this research is what is the purpose of land registration, what is the cause of illegal occupation and control of land rights / land disputes and which countries are used as objects of research on land registration related to the security of ownership of land rights that have been carried out. This research uses a literature review. The results found that there is a close relationship between the objectives of land registration activities carried out can provide security of ownership of land rights and reduce the occurrence of land disputes, and the countries used as objects of research are mostly countries prone to land conflicts.